Identification of Conflict in Short Story The Most Dangerous Game by Richard Connell - Rahmah, Fuji Alia; Pertala, Erik Candra; Hestiana, Siska (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2024)
The title taken in this study is Identification of Conflict in Short Story The Most Dangerous Game by Richard Connell. The purpose of this study is to identify the types of conflict experienced by the main character in the short story The Most Dangerous Game by Richard Connell. In this research, the writer started by collecting data by noting things related to the title of this research. The results of the research in the short story The Most Dangerous Game show that conflict plays an important role in human life as a means of changing humans for the better. In this study, there are two conflicts experienced by the main character, namely internal conflict and external conflict, external conflict is divided into two, namely physical conflict and social conflict. The approach used in this study is an objective approach with the research method used is a descriptive qualitative research method which is carried out by describing or giving an overview of the object being studied through the data collected as it is. Keywords: External conflict, Internal conflict, The Most Dangerous Game, Richard Connell